2019
DOI: 10.3390/pharmacy7020046
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Variations in Pharmacists’ Job Satisfaction in the United States

Abstract: While several studies have attested the presence of systematic gender and age variations in pharmacists’ satisfaction with their jobs, only a few of them have considered both classifications simultaneously. None have done so while systematically examining multiple facets of practitioners’ work. This article estimated U.S. pharmacists’ satisfaction levels with various facets of their work, compared them simultaneously between genders and among age groups, and tested for the presence of gender–age interaction ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
3
17
3
2
Order By: Relevance
“…It has been suggested that pharmacists' response to work-related conditions and experiences is dependent on age, with middle-age pharmacists expressing less satisfaction compared to both younger and older practitioners [17]. Our study resonated previous observations reporting that pharmacists 45 to 59 years old were more dissatisfied with their workload and attached more importance of their jobs to patients than did younger or older pharmacists [18]. We believe that this could be because senior members of the profession had prior experience to coordinate the response to past series of influenza outbreaks that were similarly been characterized by novel virus subtypes, specifically SARS outbreak of 2003, H1N1 Influenza of 2009, and New Avian Influenza Viruses H7N9 and H10N8 of 2013 [19].…”
Section: Discussionsupporting
confidence: 84%
“…It has been suggested that pharmacists' response to work-related conditions and experiences is dependent on age, with middle-age pharmacists expressing less satisfaction compared to both younger and older practitioners [17]. Our study resonated previous observations reporting that pharmacists 45 to 59 years old were more dissatisfied with their workload and attached more importance of their jobs to patients than did younger or older pharmacists [18]. We believe that this could be because senior members of the profession had prior experience to coordinate the response to past series of influenza outbreaks that were similarly been characterized by novel virus subtypes, specifically SARS outbreak of 2003, H1N1 Influenza of 2009, and New Avian Influenza Viruses H7N9 and H10N8 of 2013 [19].…”
Section: Discussionsupporting
confidence: 84%
“… 12 Our study resonated with a previous observation that pharmacists of 45 to 59 years old were more dissatisfied with their workload and attached more importance of their jobs to patients than did younger or older pharmacists. 13 We believe that this could be because senior members of the profession had prior experience to coordinate the emergency response to past series of influenza outbreaks that were similarly characterised by novel virus subtypes, specifically SARS outbreak of 2003, H1N1 Influenza of 2009, and New Avian Influenza Viruses H7N9 and H10N8 of 2013. 14 As such, they could acclimatise better to the policies and work environment for which they have served over numerous years.…”
Section: Discussionmentioning
confidence: 99%
“…No effects of gender on job satisfaction were observed in this study. However, other studies have shown that gender can affect job satisfaction and that women in general report higher levels of job satisfaction [ 16 , 39 , 40 ]. In addition, older age has also been shown to be associated with higher job satisfaction [ 11 , 14 , 19 ].…”
Section: Discussionmentioning
confidence: 99%